Elucidation of Changes in Cellulose Ultrastructure and Accessibility in Hardwood Fractionation Processes with Carbohydrate Binding Modules - Novy, Vera (ACS Sustain Chem Eng, 2020)
[Image: see text] We have recently presented a sequential treatment method, in which steam explosion (STEX) was followed by hydrotropic extraction (HEX), to selectively fractionate cellulose, hemicellulose, and lignin in hardwood into separate process streams. However, above a treatment severity threshold, the structural alterations in the cellulose-enriched fraction appeared to restrict the enzymatic hydrolyzability and delignification efficiency. To better understand the ultrastructural changes in the cellulose, hardwood chips were treated by single (STEX or HEX) and combined treatments (STEX and HEX), and the cellulose accessibility quantified with carbohydrate-binding modules (CBMs) that bind preferentially to crystalline (CBM2a) and paracrystalline cellulose (CBM17). Fluorescent-tagged versions of the CBMs were used to map the spatial distribution of cellulose substructures with confocal laser scanning microscopy. With increasing severities, STEX increased the apparent crystallinity (CBM2a/CBM17-ratio) and overall accessibility (CBM2aH6 + CBM17) of the cellulose, whereas HEX demonstrated the opposite trend. The respective effects could also be discerned in the combined treatments where increasing severities further resulted in higher hemicellulose dissolution and, although initially beneficial, in stagnating accessibility and hydrolyzability. This study suggests that balancing the severities in the two treatments is required to maximize the fractionation and simultaneously achieve a reactive and accessible cellulose that is readily hydrolyzable.